The role of digital background factors in academic achievement. A comparative study of students from three countries based on the PISA 2022 database - Csajkos, Balázs János; Kovács-Nagy, Klára (Central European Journal of Educational Research, 2025)
This study investigates the impact of students’ digital background factors on mathematical achievement using data from the 2022 PISA assessment. The analysis focuses on 15-year-old students from Austria, Estonia, and Hungary with particular attention given to the interplay between home financial conditions, ICT availability and usage, digital attitudes, and mathematics performance. Drawing on student questionnaire responses, we constructed composite indices and factor scores representing digital access, usage frequency, and digital competence at both home and school settings. Descriptive statistics, ANOVA, and linear regression models were applied to explore the relationships between digital background variables and students' mathematics proficiency scores. The results reveal that home financial status consistently predicts higher achievement across all three countries, whereas the frequency of school-based ICT use shows a negative correlation with performance. Conversely, home-based ICT usage and positive attitudes towards online platforms correlate with higher mathematics outcomes. The Estonian data challenge the initial hypothesis of a country-specific positive effect of ICT usage in schools, suggesting instead that the quality and context of digital integration matter more than frequency. The findings also highlight the importance of learning orientation and student motivation in shaping mathematics performance. Despite some methodological limitations – such as the cross-sectional nature of the data and reliance on self-reported measures – the study offers reliable insights into how digital background factors influence academic outcomes. The results underscore the need for more effective integration of ICT tools in classrooms, informed by students' learning habits and preferences.